A posthumanist critique of PRASA’s Metrorail infrastructure and its contribution to perpetuated inequalities of the majority, Hatfield, Pretoria - Devenish, Paul (University of Pretoria, 2025)
Mini Dissertation (MArch (Prof))--University of Pretoria, 2023.